2018
DOI: 10.1242/jeb.170910
|View full text |Cite
|
Sign up to set email alerts
|

Hand pressures during arboreal locomotion in captive bonobos (Pan paniscus)

Abstract: Evolution of the human hand has undergone a transition from use during locomotion to use primarily for manipulation. Previous comparative morphological and biomechanical studies have focused on potential changes in manipulative abilities during human hand evolution, but few have focused on functional signals for arboreal locomotion. Here, we provide this comparative context though the first analysis of hand loading in captive bonobos during arboreal locomotion. We quantify pressure experienced by the fingers, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
37
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

6
0

Authors

Journals

citations
Cited by 24 publications
(45 citation statements)
references
References 83 publications
5
37
0
Order By: Relevance
“…The data support our predictions concerning subarticular RBV/TV across hominid Mc1 heads ( H1a and c ) but only partially support those relating to DA ( H1 b and c ). Average RBV/TV was higher at ulno‐distal landmarks in the Mc1 head across all nonhuman great apes, consistent with a habitually adducted thumb used in pad‐to‐side or V‐pocket grips (Bardo et al, , ; Marzke et al, ; Neufuss et al, , ) and some power grasps used in African ape locomotion ( H1a ; Neufuss et al, , Samuel et al, ). Contrary to our hypothesis, however, DA was lowest at the ulno‐distal landmarks, where RBV/TV was highest, in chimpanzees, bonobos, and orangutans ( H1a ).…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…The data support our predictions concerning subarticular RBV/TV across hominid Mc1 heads ( H1a and c ) but only partially support those relating to DA ( H1 b and c ). Average RBV/TV was higher at ulno‐distal landmarks in the Mc1 head across all nonhuman great apes, consistent with a habitually adducted thumb used in pad‐to‐side or V‐pocket grips (Bardo et al, , ; Marzke et al, ; Neufuss et al, , ) and some power grasps used in African ape locomotion ( H1a ; Neufuss et al, , Samuel et al, ). Contrary to our hypothesis, however, DA was lowest at the ulno‐distal landmarks, where RBV/TV was highest, in chimpanzees, bonobos, and orangutans ( H1a ).…”
Section: Discussionsupporting
confidence: 53%
“…TMc and McP joint movement and loading is a complex product of both bony and soft tissue morphology (van Leeuwen, Vanhoof, Kerkhof, Stevens, & Vereecke, ) and compared to humans little is known of actual loads experienced by the nonhuman great ape thumb, during locomotion or manipulation (Samuel, Nauwelaerts, Stevens, & Kivell, ). However, qualitative observations of force, which was judged by how apparently resistant objects were to the grip applied, during food processing do exist for some species (Marzke, Marchant, McGrew, & Reece, ; Neufuss, Robbins, Baeumer, Hulme, & Kivell, ).…”
Section: Locomotion Manipulation and Thumb Morphologymentioning
confidence: 99%
See 1 more Smart Citation
“…) and captive settings (Wunderlich & Jungers, ; Matarazzo, ,b; Samuel et al. ) can inform predictions of frequent McP joint positions and loading across the hand in different species. Although frequent McP joint postures may only reflect part of a large and varied locomotor repertoire, previous research suggests (Tsegai et al.…”
Section: Introductionmentioning
confidence: 99%
“…In a pressure study of arboreal locomotion, Samuel et al. () found that captive bonobos used ‘palm‐back’ (64%) or ‘palm‐in’ (36%) knuckle‐walking hand postures and that peak pressure was experienced by or around the third digit. However, unlike chimpanzees (Wunderlich & Jungers, ), they did not roll radially across their digits and the fifth digit always made contact with the substrate (Samuel et al.…”
Section: Introductionmentioning
confidence: 99%